Realization of the translation of Hätte and Wäre in Cornelia Funke’s novel Tintentod - Syiam, Fanidya Hikhmatus; Tanjung, Sufriati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
The subjunctive mood in german language (Konjunktiv II) is a complex grammatical phenomenon. The problem at that phenomenon has become more interesting in the translation field. Especially if the language pair is Bahasa Indonesia because there are many ways to express the german subjunctive mood in Bahasa Indonesia. The Indonesian language has a lot of word preferences with various meanings, which must be noticed carefully. This study aims to identify the Konjunktiv II sentence, which used most common past subjunctive verbs hätte and wäre, to categorized and described Konjunktiv II sentences based on their functions. This research used descriptive qualitative. The data were the Konjunktiv II sentence collected from the fantasy novel Tintentod and their translation in Bahasa Indonesia. The data were collected through observations and note-taking techniques. The analysis technique was translational. The research results as fellows (1) there is a 418 Konjunktiv II sentence in Tintentod novel. (2) 47.4% of Konjunktiv II sentences are included in irregular Vergleichssatz categories. The translator knowledge and awareness about Konjunktiv II categories needed to achieve equivalence in subjunctive mood’s meaning.